Reviewing the Impact of Generative AI on ‎Language Learning and Teaching: A Synthesis of Potentials and Pitfalls - Hewa Fouad Ali; Zahra Abdulmutalib Muhammed (International Journal of Social Sciences & Educational Studies)
The role and implementation of Generative Artificial Intelligence (GenAI) ‎tools have encouraged ‎researchers to delve into this multifaceted area of study. ‎This thematic literature ‎review aims ‎to study the role of GenAI in education, ‎exploring the ‎challenges and ‎benefits in the context of language learning and teaching. ‎This comprehensive literature ‎review is ‎centered on thematic analysis where ‎scholarly publications were selected and ‎analyzed ‎based on predetermined ‎themes including characteristics, challenges, benefits, ‎current ‎practices, and ‎future directions of GenAI in education with a particular ‎emphasis on ‎‎language learning and teaching. The study presents the common ‎characteristics of GenAI ‎pertaining to the aspects of education. The study ‎also highlights the common challenges ‎investigated by researchers ‎such as ‎academic integrity, especially for written assignments, ‎accuracy, overreliance, ‎transparency, privacy‎, and the potential disruption of the existing ‎assessment, ‎which could diminish the perceived importance of acquiring knowledge‎ ‎‎encountered by the major stakeholders in education. The benefits of GenAI ‎include ‎providing personalized education, increasing productivity, providing ‎instant feedback, ‎creating teaching materials efficiently, and improving ‎various language aspects. Given these underlying factors, stakeholders are ‎recommended to integrate and implement GenAI in ‎their education with a ‎conscious consideration of the posed challenges and the benefits to ‎maximize ‎learning and teaching effectively. ‎